Asuhan Kebidanan Continuity of Care (COC) pada Ny.D Umur 22 Tahun G1P0A0 di PMB Minarti Pringapus - Wilisa Apriana; Rini Susanti (Universitas Ngudi Waluyo, 2025)
Continuity of care is the provision of midwifery care starting from pregnancy, childbirth, postpartum, neonate until deciding to use family planning (KB). This aims to assist, monitor, and detect the possibility of complications that accompany the mother and baby from pregnancy until the mother uses KB. The method of midwifery care at PMB Minarti is through home visits by providing counseling according to the mother's needs. Midwifery care provided to Mrs.